Food, farms, and the future: Why transforming agri-food systems is key to Viksit Bharat 2047 - Kumar, Shalander (International Crops Research Institute for the Semi-Arid Tropics, 2025)
As India embarks on its transformative journey towards becoming a developed nation by 2047, no challenge is more fundamental than reimagining how we produce, process, trade, and consume food. The statistics present a compelling narrative of both triumph and persistent challenges and vulnerability: while we produce 354 million tonnes of food grains, 367 million tonnes of horticulture, and 239.30 million tonnes of milk, generating $51.91 billion in exports, significant nutritional deficiencies persist—particularly among children under five years and women of reproductive age.